Isolation of Weizmannia coagulans and probiotic characterisation of strains - Thuy Duong Pham; Thi Lan Anh Hoang; Thi Le Quyen Tran; Thanh Trung Trinh (Vietnam Journal of Science, Technology and Engineering, 2023)
Weizmannia coagulans is a potential bacterial candidate for probiotics because of their advantageous characteristics in endospore formation, antibacterial production, and other beneficial human health effects. In this study, we isolated W. coagulans strains from different sample types collected in Hanoi and examined them for probiotic characteristics. From 40 samples, 5 strains were isolated from cow faeces. All W. coagulans strains had non-haemolytic activity and were susceptible to seven tested antibiotics. Cell-free supernatants of W. coagulans strains cultured in MRS medium could inhibit some bacterial pathogens such as Enterococcus faecalis, Listeria monocytogenes, Vibrio vulnificus, and Aeromonas dhakensis. The strains showed antioxidant activity with scavenging DPPH rates ranging from 72 to 82%. Three strains were able to adhere to the HT-29 cell line with adhesion rates ranging from 46 to 62.59%. The spores and vegetative cells of the three strains also showed great stress tolerance (survival rates >90%) against simulated gastrointestinal fluid. In liquid media containing 0.1% pancreatin and 0.3% bile salt, spores of VTCC 12782 and VTCC 12779 could germinate at rates of 25 and 2%, respectively. With the most beneficial characteristics, W. coagulans VTCC 12782 is suggested as a potential candidate for the development of probiotic products in the future.